Digitization in state administration bodies - As an important "driver" of the development of New Uzbekistan - Major Madaminov Boburjon Abrorovich (Genius Journals, 2023)
In this article, opinions were expressed about digitalization in public administration bodies.
Keywords: Digital technologies; electronic form; legal documents